Conserving dipterocarps biodiversity in remnant forests of small islands in Batam Island, Indonesia (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Susilowati A, Wijaya K, Mawazin, Rachmat HH, Lismayati Y, Kurniawan H, Ginting IM. 2024. Conserving dipterocarps biodiversity in remnant forests of small islands in Batam Island, Indonesia. Biodiversitas 25: 726-733. The protected forest of Sei Harapan is a remnant forest in Batam Island, the Riau Islands Province, Indonesia and one of the keruing (Dipterocarpus spp.) habitats on Sumatra Island. Illegal logging for its wood and land degradation have significantly reduced the keruing population. The objective of this research was to assess the diversity of keruing species and floristic composition in the Sei Harapan Protected Forest. This study employed a vegetation analysis method using purposive sampling with plotted lines and the transect placement based on the keruing position. The research revealed more than 70 species, three of which were Dipterocarpaceae species, including Vatica pauciflora, Shorea curtisii, and Dipterocarpus rigidus. D. rigidus had the highest IVI at the sapling (52.80%) and pole (67.22%). However, D. rigidus ranked 13th in the seedling stage, with an IVI of 5.79%. The diversity index was high at the seedling stage (3.73), moderate at sapling (2.25), pole (2.76), and tree stage (2.89). The evenness index was high at all growth stages, with values of 0.94 (seedling), 0.98 (sapling), 0.91 (pole), and 0.81 (tree). The richness index at the seedling, pole, and tree stage were categorized as high, with values of 10.40, 5.39, and 7.09, respectively, whereas the richness index at the sapling stage was moderate at 3.51. The study finding pointed out that the existence of Sei Harapan remnant forest requires to be preserved considering its essential function for preserving high economic value tree species, especially Dipterocarp. The comprehensive conservation effort for dipterocarps species, is crucial considering the research findings revealed a problem of continuity of species regeneration and the emergence of new pioneer species as the consequence of anthropogenic disturbance.
Keywords: Dipterocarpus rigidus, diversity, floristic composition, habitat